Efficiency of resonating compounds of Aminophenols as corrosion inhibitors for reinforced concrete under carbonated environment - Sharma, Uday (My University, 2019)
The steel reinforcement in concrete has an inherent property of forming an oxide layer which inhibits corrosion causing reactions of steel with air and moisture. This passive oxide layer is facilitated by the alkaline nature of the concrete. However, with permeation of carbon-dioxide, the calcium hydroxide in concrete reacts with carbon-dioxide to form neutral calcium carbonate compounds which results in gradual breakdown of protective oxide layer. Many single-chained organic compounds containing -NH2 as a functional group are used as commercial corrosion inhibitors in concrete. In this research, the corrosion inhibiting properties of generic compounds 2-Aminophenol, 3-Aminophenol and 4-Aminphenol which are resonating structures containing cyclic double bond and -NH2 as a functional group, were tested. Electrochemical tests (Half-cell potential and linear polarization resistance) were conducted on steel samples immersed in synthetic carbonated pore-solution for 24 hours, 72 hours, 120 hours and 240 hours with the chemicals individually at three different concentrations: 0.01 M, 0.05M and 0.1M. Further, to test their effectiveness as migratory corrosion inhibitors, carbonation depth test and sorptivity test were conducted on concrete samples and electrochemical tests (Half-cell potential and linear polarization resistance) were conducted on reinforced concrete samples treated with chemical at concentration of 1M. All the three chemicals were very successful in reducing probability of corrosion in steel samples immersed in carbonated synthetic pore-solution at all concentration level. 2-Aminophenol was slightly more effective than 3-Aminophenol, while 4-Aminophenol was least effective in inhibiting corrosion of steel samples in pore solution. 0.05M was the optimum concentration of chemicals in pore solution. As surface applied inhibitor, 4-Aminophenol was most efficient. Results indicated that position of functional group plays an important role in altering properties of reinforced concrete. The ortho position of amine group had better chelate formation leading to reduction in corrosion current density. On the other hand, para position of amine group had better penetration ability, making chemical most efficient as migratory corrosion inhibitor.
Keywords: corrosion inhibitors; corrosion monitoring; positioning; aminophenols; pore solution